Association of body mass index and hypoglycemia with mortality rates among sepsis patients: A retrospective sub‐analysis of the FORECAST study - Atsushi Tanikawa; Daisuke Kudo; Hiroyuki Ohbe; Shigeki Kushimoto (Acute Medicine & Surgery, 2023)
Abstract Aim Hypoglycemia at admission is associated with high mortality in sepsis patients. However, the influence of body mass index (BMI) on this association remains unknown. Therefore, this study assesses the association of hypoglycemia at admission with mortality in patients with sepsis according to BMI. Methods This was a secondary analysis of a multicenter, prospective cohort study of 59 intensive care units in Japan. We included 1184 patients (age ≥16 years) with severe sepsis and excluded those with missing data on glucose level, BMI, or survival at discharge. The initial blood glucose level of <70 mg/dL was defined as hypoglycemia. Patients were assigned to the hypoglycemia or non‐hypoglycemia group as per BMI category (<18.5 [low], 18.5–24.9 [normal], and ≥25 [high] kg/m2). The main outcome was in‐hospital mortality. Multivariate logistic regression models were used to evaluate BMI category‐by‐hypoglycemia interactions. Results Overall, 1103 patients, including 65 with hypoglycemia, were analyzed. In the normal BMI group, patients with hypoglycemia had a higher in‐hospital mortality rate (18/38, 47.4%) than those without (119/584, 20.4%). There was a significant interaction between normal BMI and hypoglycemia affecting in‐hospital mortality; however, this effect was not observed for other BMI categories (odds ratio, 2.32; 95% confidence interval, 1.05–5.07; p‐value for interaction = 0.0476). Conclusion The relationship between patients with sepsis and hypoglycemia on admission may differ according to BMI. Hypoglycemia on admission may be associated with high mortality in patients with normal BMI, but not in those with low or high BMI.